2011
DOI: 10.1007/dcr.0b013e318205e116
|View full text |Cite
|
Sign up to set email alerts
|

Anal Metastasis of Colorectal Carcinoma Origin: Implications for Diagnosis and Treatment Strategy

Abstract: Treatment strategies for anal metastasis of colorectal carcinoma origin should consider the mechanism of metastasis. Patients with suspected lymphovascular metastasis should undergo radical resection beyond the primary and metastatic anal tumor to eradicate remnant cancer cells, together with preoperative chemoradiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The pattern of metastases to the anus is implanted or lymphovascular metastases [12]. Implantation of rectal carcinoma cells has often been reported in the last half century.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of metastases to the anus is implanted or lymphovascular metastases [12]. Implantation of rectal carcinoma cells has often been reported in the last half century.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal cancer cells are able to metastasize to the anal fistula [13,14], biopsy wounds [15], suture lines [16-18], and obstructive colitis [19]. Lymphovascular metastasis in the literature is defined as anorectal metastatic cancer with an intact anorectal epithelium [12]. In this case, the histological findings showed that small white nodules, consisting of cancer cells, existed in the lymphatic vessels of the submucosa and muscularis mucosae, but not on the mucosa (Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rectal carcinoma with synchronous anal metastasis is extremely rare [3], is difficult to diagnose, and no standardized therapeutic strategy exists [4]. In the present case, we performed local resection of the anal tumor to determine whether it was a primary cancer or represented metastasis of the rectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the cases had a history of anal fistulas or fissures. The optimal surgical procedure for colorectal cancer with anal metastasis has been controversial [4, 6, 7]. For the purpose of radical resection, APR has been performed in some cases, particularly in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation